2015
DOI: 10.1016/j.bjid.2014.10.004
|View full text |Cite
|
Sign up to set email alerts
|

São Paulo urban heat islands have a higher incidence of dengue than other urban areas

Abstract: Urban heat islands are characterized by high land surface temperature, low humidity, and poor vegetation, and considered to favor the transmission of the mosquito-borne dengue fever that is transmitted by the Aedes aegypti mosquito. We analyzed the recorded dengue incidence in Sao Paulo city, Brazil, in 2010-2011, in terms of multiple environmental and socioeconomic variables. Geographical information systems, thermal remote sensing images, and census data were used to classify city areas according to land sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
87
0
14

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(111 citation statements)
references
References 31 publications
4
87
0
14
Order By: Relevance
“…Most cities including São Paulo show a greater heat island effect such as increased rate of infectious disease and much higher mortality during heat waves enhanced by the urban heat island (Araujo et al, 2015; Tan et al, 2010). Urbanization is increasing rapidly worldwide (Allender et al, 2011), which could exacerbate the effect of heat in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Most cities including São Paulo show a greater heat island effect such as increased rate of infectious disease and much higher mortality during heat waves enhanced by the urban heat island (Araujo et al, 2015; Tan et al, 2010). Urbanization is increasing rapidly worldwide (Allender et al, 2011), which could exacerbate the effect of heat in the future.…”
Section: Discussionmentioning
confidence: 99%
“…The influence of urbanisation on dengue transmission was investigated in Pakistan , Taiwan , Mexico , Costa Rica and Brazil . In these studies, urbanisation was defined by the proportion of people living in urban areas , urban heat island or by some socioecological factors .…”
Section: Resultsmentioning
confidence: 99%
“…Most of these studies found a significant association between dengue and high population density. However, a single study in Argentina reported that rural areas with a low population density may experience severe epidemics in the absence of a tap water supply .…”
Section: Resultsmentioning
confidence: 99%
“…A viabilidade do vetor na cidade de São Paulo e o risco de ocorrência de grandes epidemias decorrentes da adaptação do mosquito às condições adversas a ele presentes na cidade foram hipotetizadas por Louise, Vidal e Suesdek (2015), assim como a existência de associação entre o maior risco de ocorrência de dengue e as ilhas urbanas de calor da cidade, as quais apresentariam condições mais adequadas para a proliferação de Aedes aegypti e a transmissão do vírus dengue (Araujo et al, 2015).…”
Section: Aedes Aegypti E Arbovirosesunclassified